Wars of Conquest and Independence - Roland Hodler; Hadi Yektas (Center for Economic Studies and ifo Institute (CESifo), 2013)
Wars of conquest and wars of independence are characterized by an asymmetric payoff structure: one party gets aggregate production if it wins, and its own production if it loses, while the other party gets only its own production if it wins, and nothing if it loses. We study a model of war with such an asymmetric payoff structure, and private information about military technologies. We characterize continuous equilibrium strategies and find that the party that gets aggregate production when winning fights aggressively only if its military technology is relatively good, while the other party fights quite aggressively even if its military technology is relatively poor. From an ex ante perspective, this other party is therefore more likely to win the war unless its expected military technology is considerably worse. Our model may thus explain why defending countries and secessionist groups often win against much larger opponents.
Keywords: D74; H56; 330; conflict; war; asymmetric contests; private information